1999
DOI: 10.1046/j.1365-2141.1999.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Thrombocytopenia After Treatment With Campath 1h in a Patient With Chronic Lymphocytic Leukaemia

Abstract: In conclusion, deferiprone and DFO therapy on alternate days may improve compliance with chelation therapy. A negative iron balance can be achieved with this regimen and it may well be cost-effective. A larger prospective randomized study evaluating this model over a longer period of time seems necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…If antigen binding on clonal B cells is important, this is not because of direct antibody production, but immune response to the antigen should be mediated by other cells in the microenvironment, and this is the case of T cells. Given that the course of CLL is typically characterized by profound immunosuppression, with T-cell function impairment and altered immune surveillance, both the microenvironment and cell-to-cell interactions are likely to be implicated in the emergence of nonneoplastic autoreactive B and T cells (12,39,(41)(42)(43)(44). Murine and human studies on autoimmune hemolytic anemia have shown that autoreactive T-helper (T H ) cells are critical for the induction of the autoimmune phenomena (21).…”
Section: Discussionmentioning
confidence: 99%
“…If antigen binding on clonal B cells is important, this is not because of direct antibody production, but immune response to the antigen should be mediated by other cells in the microenvironment, and this is the case of T cells. Given that the course of CLL is typically characterized by profound immunosuppression, with T-cell function impairment and altered immune surveillance, both the microenvironment and cell-to-cell interactions are likely to be implicated in the emergence of nonneoplastic autoreactive B and T cells (12,39,(41)(42)(43)(44). Murine and human studies on autoimmune hemolytic anemia have shown that autoreactive T-helper (T H ) cells are critical for the induction of the autoimmune phenomena (21).…”
Section: Discussionmentioning
confidence: 99%
“…Few cases of severe thrombocytopenia arising as a complication of alemtuzumab therapy for disorders other than MS have been published [20][21][22][23] despite its approval for the treatment of CLL a decade ago and its growing off-label use in a variety of settings such as hematopoietic and solid organ transplantation. Several reports even document the effective use of alemtuzumab for the treatment of ITP and other autoimmune cytopenias.…”
Section: Discussionmentioning
confidence: 99%
“…52 There have been 2 reports of fatal refractory ITP after treatment of chronic lymphocytic leukemia with alemtuzumab. 53,54 In 3 cases, ITP (one case fatal) occurred during a clinical trial of alemtuzumab for MS. 55 As with the published reports, we have found the autoimmune cytopenias developing after alemtuzumab and auto-HSCT to be generally severe and refractory to steroid therapy alone. All our patients required multiple agents to treat the cytopenias, and demonstrated a response to rituximab, which appears to be an effective agent in refractory cases.…”
Section: Discussionmentioning
confidence: 99%